1973
DOI: 10.1007/bf01869992
|View full text |Cite
|
Sign up to set email alerts
|

A study of passive potassium efflux from human red blood cells using ion-specific electrodes

Abstract: Summary. Using ion-specific electrodes, the potassium leakage induced by ouabain in human erythrocytes can be measured continuously and precisely near physiological conditions. Upon small additions of isotonic sucrose solution to a suspension of red cells in physiological saline the passive potassium efflux increases proportionally to the chloride ratio. The same result is obtained upon addition of hypertonic sucrose solution, suggesting that neither osmolarity nor intracellular concentrations have any influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…He proposed that as the pH increases in these channels, hydrogen ions are liberated, and finally, at very high pH, the charge barrier is so diminished or reversed as to allow the passage of cations. Mond (1927), Passow (1964), Wilbrandt and Schatzmann (1960), La Celle and Rothstein (1966), Donlon and Rothstein (1969), and Morel (1973) found that the rates of cation efflux increased at low external anion concentrations . This was not due solely to an increase in the driving force for cation efflux because of the change in membrane potential, but also represented a true increase in the apparent cation permeability .…”
Section: Introductionmentioning
confidence: 99%
“…He proposed that as the pH increases in these channels, hydrogen ions are liberated, and finally, at very high pH, the charge barrier is so diminished or reversed as to allow the passage of cations. Mond (1927), Passow (1964), Wilbrandt and Schatzmann (1960), La Celle and Rothstein (1966), Donlon and Rothstein (1969), and Morel (1973) found that the rates of cation efflux increased at low external anion concentrations . This was not due solely to an increase in the driving force for cation efflux because of the change in membrane potential, but also represented a true increase in the apparent cation permeability .…”
Section: Introductionmentioning
confidence: 99%